2019
DOI: 10.1073/pnas.1817248116
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipolysis of immune-activating ligands promotes evasion of innate defenses

Abstract: Commensal and pathogenic bacteria hydrolyze host lipid substrates with secreted lipases and phospholipases for nutrient acquisition, colonization, and infection. Bacterial lipase activity on mammalian lipids and phospholipids can promote release of free fatty acids from lipid stores, detoxify antimicrobial lipids, and facilitate membrane dissolution. The gram-positive bacterium Staphylococcus aureus secretes at least two lipases, Sal1 and glycerol ester hydrolase (Geh), with specificities for short- and long-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 110 publications
1
83
0
Order By: Relevance
“…First, prior work from our laboratory in a mouse model of S. aureus catheterassociated biofilm infection also demonstrated a TLR9independent phenotype [22], confirming the findings obtained during craniotomy infection. Second, as previously mentioned, numerous S. aureus virulence determinants have recently been identified that interfere with TLR2 recognition or signaling [46][47][48][49]; however, to date, no S. aureus inhibitors of TLR9-dependent pathways have been reported. By extension, this suggests that TLR2-mediated recognition of S. aureus is more relevant for bacterial clearance, since this pathway has been extensively targeted by the organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, prior work from our laboratory in a mouse model of S. aureus catheterassociated biofilm infection also demonstrated a TLR9independent phenotype [22], confirming the findings obtained during craniotomy infection. Second, as previously mentioned, numerous S. aureus virulence determinants have recently been identified that interfere with TLR2 recognition or signaling [46][47][48][49]; however, to date, no S. aureus inhibitors of TLR9-dependent pathways have been reported. By extension, this suggests that TLR2-mediated recognition of S. aureus is more relevant for bacterial clearance, since this pathway has been extensively targeted by the organism.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is critical for S. aureus containment during craniotomy infection, but is not sufficient for bacterial clearance, since biofilm infections persist in an immune competent host during craniotomy infection. Prior studies have identified several molecules that are produced by planktonic S. aureus that interfere with TLR2-dependent recognition, including lipase (Geh) [46], staphylococcal superantigenlike protein 3 (SSL3) [47], and molecular mimicry via blocking the Toll-interacting receptor (Tir) domain of TLR2 [48,49]. In addition, the paired-immunoglobulinlike receptor (PIR)-B contains an inhibitory immunoreceptor tyrosine-based inhibition (ITIM) motif that upon binding S. aureus lipoteichoic acid, dampens proinflammatory cytokine production [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…C-terminally 6xHis-tagged S.aureus Geh was expressed in E. coli lysY/I q and purified as described previously (56).…”
Section: Methodsmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are a specific family of PRRs for host cells to recognize different PAMPs. TLR2-based signaling in response to S. aureus infection plays a critical role in the initiation of an effective innate response (Chen and Alonzo, 2019). During S. aureus infection, PAMPs recognized by TLR2 trigger the production of inflammatory mediators such as interleukin (IL)-6, tumor necrosis factor (TNF)-a, IL-1b, nitric oxide (NO), chemokines, interferons, and IL-10 through the activation of TLR2-mediated nuclear factor kB (NF-kB), mitogen-activated protein kinase (MAPK), and phosphatidylinositol 3 kinase (PI3K)/Akt pathways (Takeuchi and Akira, 2010).…”
Section: Introductionmentioning
confidence: 99%